Moving Up and Down the Ladder: Perceived Social Mobility and Emotional Dispositions Among South Florida's Immigrants. Issue 4 (5th October 2017) - Vaquera, Elizabeth; Aranda, Elizabeth
Abstract : Migrating to a new country is often associated with difficulties such as social isolation, financial strain, language barriers, and cultural differences. Less is known about how social mobility brought about by migration may be related to the emotional dispositions of immigrants (also referred to as subjective well‐being). To examine this relationship, we utilize data from a representative sample of 1, 268 first‐generation immigrants from 80 different countries living in South Florida. Changes in perceived social mobility between the homeland and the United States—moving up and down the socioeconomic ladder—are indeed associated with differences in immigrants' negative dispositions. We draw from literature on expectations, social comparisons, and subjective class status to explain these findings. We do not find a statistically significant association between changes in socioeconomic status and positive dispositions, which may suggest that losses outweigh migration‐related gains. Additionally, findings reveal that nondominant groups fare worse than Cubans (the dominant group in the region) with regard to dispositions. Social comparisons to the dominant ethnic group may explain this, as well as perceptions of relative deprivation experienced by groups not favored by immigration policies and underrepresented in social and economic institutions. We conclude by discussing implications on how negative emotional dispositions represent risk factors that could affect immigrants' mental health.